Analytical-numerical procedure incorporating cracking in RC beams. Issue 5 (1st July 2014) - Patel, K.A.; Chaudhary, Sandeep; Nagpal, A.K.
Abstract : Purpose: – The purpose of this paper is to develop, for use in everyday design, a procedure that incorporates the effect of concrete cracking in reinforced concrete (RC) beams at service load and requires computational efforts which is a fraction of that required for the available methods. Further for ease of use in everyday design the reinforcement input data is minimized. The procedure has been demonstrated for continuous beams and is under development for tall building frames. Design/methodology/approach: – The procedure is analytical at the element level and numerical at the structural level. A cracked span length beam element consisting of three cracked zones and two uncracked zones has been used. Closed form expressions for flexibility coefficients, end displacements, crack lengths, and mid-span deflection of the cracked span length beam element have been presented. In order to keep the procedure analytical at the element level, average tension stiffening characteristics are arrived at for cracked zones. Findings: – The proposed procedure, at minimal computation effort and minimal reinforcement input data, yields results that are close to experimental and finite element method results. Practical implications: – The procedure can be used in everyday design since it requires minimal computational effort and minimal reinforcement input data. Originality/value: – A procedure that requires minimal computational effort and minimal reinforcement input data for incorporating concrete cracking effects in RC structures at service load has been developed for use in everyday design.